Coerência e argumentação em comentários do Facebook - Murayama, Rosana de Castro Januario (2020)
This work aims to analyze the coherence and argumentative orientation in Facebook comments and it bases on referencing and the discursive topic. This investigation focuses on the theoretical contribution of Textual Linguistics, from a sociocogni